Psychoactive drug use by medical students: a review of the national and international literature - Mesquita, Ana Maria [UNESP]; Laranjeira, Ronaldo [UNESP]; Dunn, John [UNESP] (Associação Paulista de Medicina - APM, 1997)
Non-medical drug use among medical students is a major concern among researchers and policy makers in several countries, not only because of the personal harmful consequences that may arise from this behavior, but also for the social consequences. This article aims to evaluate national and international data available on non-medical drug-use among medical students and risk factors associated with these problems, as well as social and institutional implications. Prevalence rates, in Brazilian and international samples, of alcohol and drug use, abuse and dependence, reasons for onset, methodological issues, and the role of medical education are presented, compared and discussed. The authors suggest some issues that should be a addressed in order to deal with this complex situation.

Problemas relacionados ao uso não-médico de substâncias psicoativas por estudantes de medicina tem apresentado um interesse crescente por parte de vários setores da comunidade, não apenas pelas possíveis consequências pessoais deste uso, mas também pelas conseqüências sociais. O presente artigo tem como objetivo avaliar dados nacionais e internacionais de uso neo-médico de substâncias psicoativas por estudantes de medicina, bem como fatores de risco para problemas relacionados a este uso e implicações sociais e institucionais. Tópicos como prevalências de uso, abuso e dependência, questões metodológicas, razões para uso, bem como o papel das escolas médicas são discutidos. Os autores apresentam sugestões para abordagem científica e técnica de problemas relacionados ao uso de drogas por esta população.
Keywords: Drugs; medical students; dependency; prevention and medical education